The NEWTON-g Gravity Imager: Toward New Paradigms for Terrain Gravimetry - Carbone, D.; Antoni-Micollier, L.; Hammond, G.; de Zeeuw - van Dalfsen, E.; Rivalta, E.; Bonadonna, C.; Messina, A.; Lautier-Gaud, J.; Toland, K.; Koymans, M.; Anastasiou, K.; Bramsiepe, S.; et al. (Frontiers in Earth Science, 2020)
Knowledge of the spatio-temporal changes in the characteristics and distribution of subsurface fluids is key to properly addressing important societal issues, including: sustainable management of energy resources (e.g., hydrocarbons and geothermal energy), management of water resources, and assessment of hazard (e.g., volcanic eruptions). Gravimetry is highly attractive because it can detect changes in subsurface mass, thus providing a window into processes that involve deep fluids. However, high cost and operating features associated with current instrumentation seriously limits the practical field use of this geophysical method. The NEWTON-g project proposes a radical change of paradigm for gravimetry through the development of a field-compatible measuring system (the gravity imager), able to real-time monitor the evolution of the subsurface mass changes. This system includes an array of low-costs MEMS-based relative gravimeters, anchored on an absolute quantum gravimeter. It will provide imaging of gravity changes, associated with variations in subsurface fluid properties, with unparalleled spatio-temporal resolution. During the final ~2 years of NEWTON-g, the gravity imager will be field tested in the summit of Mt. Etna volcano (Italy), where frequent gravity fluctuations, easy access to the active structures and the presence of a multiparameter monitoring system (including traditional gravimeters) ensure an excellent natural laboratory for testing the new tools. Insights from the gravity imager will be used to (i) improve our knowledge of the cause-effect relationships between volcanic processes and gravity changes observable at the surface and (ii) develop strategies to best incorporate the gravity data into hazards assessments and mitigation plans. A successful implementation of NEWTON-g will open new doors for geophysical exploration.